COLLABORATIVE GOVERNANCE DALAM PENGELOLAAN BADAN USAHA MILIK DESA MENUJU PENCAPAIAN SUSTAINABLE DEVELOPMENT GOALS, STUDI DESA BATU RADEN, KECAMATAN LUBUK RAJA, KABUPATEN OGAN KOMERING ULU - Putri Yolanda; Yahnu Wiguno Sanyoto; Eva Susanti; Aprilia Lestari (PT. Hasba Edukasi Mandiri, 2026)
Collaborative Governance in the management of the Village-Owned Enterprise revolving savings and loan program in Batu Raden Village, Lubuk Raja Sub-district, Ogan Komering Ulu Regency is motivated by issues of delayed loan repayments and the need to strengthen collaboration among actors in supporting the Village Sustainable Development Goals. This study aims to analyze the collaboration process between the Village Government, Village-Owned Enterprise, Village Consultative Body, and the community in the management of Village-Owned Enterprise.This research uses a qualitative method with a descriptive approach through data collection techniques including interviews, observation, and documentation in Batu Raden Village. The results show that collaborative governance has been implemented quite well through supportive initial conditions, facilitative leadership, clear institutional design, and a collaborative process involving communication and deliberation among actors. This study indicates that the management of the revolving savings and loan Village-Owned Enterprise has contributed to the achievement of Village SDGs, particularly decent work and economic growth as well as partnerships for the goals, although improvements are still needed in socialization and coordination to achieve more optimal results.